2020
DOI: 10.1007/s13337-020-00571-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural, glycosylation and antigenic variation between 2019 novel coronavirus (2019-nCoV) and SARS coronavirus (SARS-CoV)

Abstract: The emergence of 2019 novel coronavirus (2019-nCoV) is of global concern and might have emerged from RNA recombination among existing coronaviruses. CoV spike (S) protein which is crucial for receptor binding, membrane fusion via conformational changes, internalization of the virus, host tissue tropism and comprises crucial targets for vaccine development, remain largely uncharacterized. Therefore, the present study has been planned to determine the sequence variation, structural and antigenic divergence of S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
250
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 213 publications
(260 citation statements)
references
References 28 publications
7
250
0
3
Order By: Relevance
“…So far, studies have not been conducted that reveal the peptide presentation. However, CTL epitopes of SARS-CoV-2 have been predicted by several studies, which may be used for understanding the pathogenesis and development of peptide-based vaccines (Kumar et al 2020;Walls et al 2020). Studies have been conducted in SARS-CoV-2 infected patients showing the activation and reduction in CD4 + and CD8 + T cell counts (Li et al 2020a).…”
Section: Host Immune Response Against Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…So far, studies have not been conducted that reveal the peptide presentation. However, CTL epitopes of SARS-CoV-2 have been predicted by several studies, which may be used for understanding the pathogenesis and development of peptide-based vaccines (Kumar et al 2020;Walls et al 2020). Studies have been conducted in SARS-CoV-2 infected patients showing the activation and reduction in CD4 + and CD8 + T cell counts (Li et al 2020a).…”
Section: Host Immune Response Against Sars-cov-2mentioning
confidence: 99%
“…S protein is responsible for the attachment and entry of SARS-CoV-2 to the host target cell receptor, probably angiotensin-converting enzyme 2 (ACE2) mainly expressed on alveolar epithelial type II (AECII) cells, including extrapulmonary tissues such as heart, kidney, endothelium, and intestine ). SARS-CoV-2 has been shown to exhibit novel glycosylation sites in the spike glycoprotein of 2019-nCoV, suggesting that the virus may utilize different glycosylation sites to interact with its receptors (Kumar et al 2020). Studies have demonstrated that SARS-CoV-2 spike protein has higher affinity to the ACE2 receptor as compared with SARS (Walls et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The virus infection leads to 245,922 confirmed cases and 10,048 deaths worldwide as of March 20, 2020(ProMED-mail 2020. SARS-CoV-2 and SARS are clinically similar, and recent studies have shown that SARS-CoV-2 is closely related to SARS-CoV (Kumar et al 2020). The cause and spread of SARS-CoV-2 outbreak are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, C-type lectin DC-SIGN and L-SIGN can enhance viral entry via their binding to the S protein glycans (Han et al, 2007; Jeffers et al, 2004). Therefore, numerous antiviral strategies have been designed to interfere protein glycosylation or glycan-based interaction (Shih et al, 2006; Vincent et al, 2005; Zheng et al, 2020; Zhou et al, 2010), and glycosylation is considered as a key aspect to develop effective vaccine (Chen et al, 2014; Kumar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%